Study of rheological flow curves of ED20 emulsions - Ochilov, Akbarjon; Urinboyeva, Marifatoy; Abdikamolova, Aziza; Kuldasheva, Shakhnoza; Eshmetov, Izzat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article discusses the main properties of ED20 emulsions - its rheological characteristics and determines the shear stress at different shear rates, the strengthening effect on the structure of the emulsion. Methods. To establish the rheological properties and characteristics of resinous substances and their curing processes, viscometric studies were carried out using the Reotest-2.1 device. To do this, the composition under study was placed in a wedge-shaped slot between a stationary plate and a cone, the width of which has a diameter d. The process was carried out at different temperatures and the values of the parameter α were calculated. Results. Rheological studies of epoxy resin emulsions with different concentrations of LABSA (linear alkylbenzenesulfonic acid) show that these systems have structured non-Newtonian properties. At all analyzed levels of epoxy resin, an increase in the proportion of emulsifier leads to an increase in rheological parameters such as ultimate shear stress, viscosity and others. Conclusion. The rheological characteristics of ED20 emulsions demonstrate non-Newtonian behavior, characterized by a decrease in viscosity with increasing shear rate. This effect is especially pronounced when using PEG and LABSA as emulsifiers, which emphasizes their importance in stabilizing emulsion systems and the need for careful selection of surfactants depending on the target properties of the finished products.